Pengaruh Penyuluhan dengan Boneka Tangan Terhadap Pengetahuan dalam Menyikat Gigi Siswa Kelas IV SD Negeri 58 Kota Banda Aceh - Naila Sharfina; Nasri Nasri (Lembaga Pengembangan Kinerja Dosen, 2024)
Oral health is a problem that needs comprehensive handling because it will have many impacts. Therefore, counseling is needed to help provide knowledge in brushing teeth, especially in children. Many interesting media are used in counseling such as hand puppets. The use of hand puppets is intended because children like to learn while playing. The results of the initial examination of fourth grade students of SD Negeri 58 Banda Aceh City using the DMF-T index, that the dental caries status of students was 4.5 with a high category. This study aims to determine the effect of counseling with hand puppets on knowledge in brushing teeth of fourth grade students of SD Negeri 58 Kota Banda Aceh. Using the Quasi Experiment method and one group pre-post test design. The study was conducted on the population, namely all fourth grade students of SD Negeri 58 Kota Banda Aceh, totaling 40 people. Data analysis using paired T-test. The results showed that knowledge before counseling with hand puppets was 1.35 increased to 1.88 with a p value of 0.001. There is a significant effect on counseling with hand puppets on knowledge in brushing teeth of fourth grade students of SD Negeri 58 Kota Banda Aceh.